2014
DOI: 10.1097/mop.0000000000000144
|View full text |Cite
|
Sign up to set email alerts
|

International adoption of children with birth defects

Abstract: Although the health of children involved in international adoption has been well studied, there is a lack of information about the experiences of the adoptive parents of children with birth defects. We discuss a pilot study conducted on adoptive parents of children with a specific birth defect, orofacial clefting, and discuss areas for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…In this study in a referral unit in Spain, we confirmed that most of the children with special needs seen in our unit were of Asian origin (96.5%), as previously reported by other groups [ 4 ]. It was found that the pathologies that led to IA via SN were confirmed in most cases, especially when those were major surgical conditions (digestive tract, cardiac, or palatal malformations).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study in a referral unit in Spain, we confirmed that most of the children with special needs seen in our unit were of Asian origin (96.5%), as previously reported by other groups [ 4 ]. It was found that the pathologies that led to IA via SN were confirmed in most cases, especially when those were major surgical conditions (digestive tract, cardiac, or palatal malformations).…”
Section: Discussionsupporting
confidence: 91%
“…With the general decline in number, the proportion of children adopted presenting pre-existing conditions has increased in Spain and other countries, such as France and the United States [ 2 , 3 ]. The definition of “special needs” (SN) arises from the urgency of speeding up the adoption of minors with chronic pathologies requiring evaluation and treatment in a short period [ 4 ]. Heart defects, orthopedic problems, infectious diseases, or neurodevelopmental disorders are among the most prevalent diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In this study in a referral unit in Spain, we con rmed that most of the children seen in our Unit were of Asian origin (96.5%), as previously reported 4 . It was found that the pathologies that led to IA via SN were con rmed in a high percentage of cases, especially when those were major surgical conditions (digestive, cardiac, or palatal malformations).…”
Section: Discussionsupporting
confidence: 87%
“…11 Medical concerns could include one or more congenital anomaly (because children with birth defects are more likely to be candidates for adoption in international countries), nutritional deficiencies, or infectious diseases. 9,10 In addition, children with disabilities may have feeding challenges or may require specialized diets or additional support at mealtimes, which may be difficult depending on the preadoption environment. 11 Although specific data were not available in our cohort, anecdotal reports from the pediatricians in our institution's international adoption clinic indicate that the proportion of children with complex medical problems at the time of adoption have increased, which may account for the trend seen with lower anthropometric measures over time, although this cannot be clearly attributed to overall health.…”
Section: Discussionmentioning
confidence: 99%
“…Thousands of children are adopted internationally to the United States each year, and it is estimated that only 20% have no special medical or developmental concerns, whereas 60% have at least one mild to moderate problem and 20% have one or more severe problems 11 . Medical concerns could include one or more congenital anomaly (because children with birth defects are more likely to be candidates for adoption in international countries), nutritional deficiencies, or infectious diseases 9,10 . In addition, children with disabilities may have feeding challenges or may require specialized diets or additional support at mealtimes, which may be difficult depending on the preadoption environment 11 .…”
Section: Discussionmentioning
confidence: 99%